In-silico identification and In-Vitro Anti-Psoriatic Evaluation of the Ethanolic Extract of Hemidesmus indicus (L.) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Psoriasis is a chronic, relapsing, immune-mediated inflammatory skin disorder driven by keratinocyte hyperproliferative and epidermal hyperplasia. Conventional therapies control symptoms but they are limited by adverse effects, high cost and recurrence after discontinuation, motivating interest in plant-derived alternatives. Hemidesmus indicus (L.) R.Br (Indian sarsaparilla) is traditionally used for chronic skin disorders and reported to contain anti-inflammatory and anti-oxidant phytoconstituents, but direct evidence of anti-psoriatic activity on keratinocytes has not previously been reported. The study aims to perform phytochemical screening of Hemidesmus indicus root extracts and evaluate the in vitro and in silico anti-psoriatic activity of the ethanolic extract on HaCaT human keratinocytes. The anti-proliferative effect of the ethanolic extract on HaCaT keratinocytes was assessed by MTT assay after 24-48 hours and showed positive for eight phytoconstituents, while the petroleum ether fraction was positive only for terpenoids and steroids. To provide mechanistic support for this activity, phytoconstituents of H. indicus were retrieved from the IMPPAT database and filtered through a machine-learning-based screening pipeline, yielding the top 15 candidates for molecular docking against six anti-psoriatic targets (TNF, TYK2, PDE4B, NR3C1, IL17RA and AHR). 16-Dehydropregnenolone, Benzophenone emerged as the top-scoring leads, with binding affinities of −8.9, -8.0 kcal/mol respectively (mean −8.9 kcal/mol), outperforming the remaining screened candidates across the target panel. These in-silico findings converge with the observed in-vitro anti-proliferative activity, providing mechanistic support for the ethanolic extract's effect and reinforcing H. indicus as a candidate multi-target anti-psoriatic phytotherapeutic agent that warrants further mechanistic and in-vivo evaluation.
Keywords: Hemidesmus indicus; Psoriasis; Phytochemical screening; HaCaT keratinocytes; MTT assay; Anti-proliferative activity